Characterization of drought stress-responsive root transcriptome of faba bean (Vicia faba L.) using RNA sequencing - Alghamdi, Salem S. (3 Biotech, 2018)
Drought and salinity are the major factors that limit the faba bean (Vicia faba L.) production worldwide. The aim of this study is to identify the water stress differentially expressed genes (DEGs) through the root transcriptome analyses of the drought-tolerant Hassawi 2 genotype at vegetative and flowering stages. A total of 624.8 M high-quality Illumina reads were generated and assembled into 198,155 all-unigenes with a mean length of 738 bp and an N50 length of 1347 bp. Among all-unigenes, 78,262 were assigned to non-redundant (Nr), 66,254 to nucleotide (Nt), 54,034 to KEGG, and 43,913 to gene ontology (GO) annotations. A total of 36,834 and 35,510 unigenes were differentially expressed at the vegetative and flowering stages of Hassawi 2 under drought stress, respectively. The majority of unigenes were down-regulated at both developmental stages. However, the number of genes up-regulated (15,366) at the flowering stage exceeded the number of those up-regulated (14,097) at the vegetative stage, and the number of genes down-regulated (20,144) at the flowering stage was smaller than the number of those down-regulated (22,737) at the vegetative stage. The drought stress-responsive differentially expressed unigenes coded for various regulatory proteins, including protein kinases and phosphatases, transcription factors and plant hormones and functional proteins including enzymes for osmoprotectant, detoxification and transporters were differentially expressed, most of which were largely up-regulated. Moreover, a substantial proportion of the DEGs identified in this study were novel, most exhibited a significant change in their expression levels under water stress, making them an unexploited resource that might control specific responses to drought stress in the faba bean. Finally, qRT-PCR results were found almost consistent with the results of next-generation sequencing. Our data will help in understanding the drought tolerance mechanisms in plants and will provide resources for functional genomics. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13205-018-1518-2) contains supplementary material, which is available to authorized users.